Pengembangan Bahan Ajar Aqidah Akhlak Berbasis Inkuiry Terbimbing - Pujilestari, Alifah; Romdloni, Romdloni (JUPIN (Jurnal Pendidikan Islam Nusantara), 2023)
The development of guided inquiry-based Aqidah Akhlak teaching materials is a new breakthrough learning that creates products as learning media. This development aims to see how the effectiveness of Aqidah Akhlak teaching media and to find out the model for the development of Aqidah Akhlak teaching materials based on guided inquiry. This product development was carried out because the school in its religious-based lessons had not yet implemented additional learning media such as this teaching material. At the school used by this researcher the learning process still uses printed books only. The research method used is the development method or Research and Development (R&D). In this study, a product that was successfully developed by researchers was in the form of guided inquiry-based Aqidah Akhlak teaching materials on the morals of adolescent association in class XI MA. This research study is in the form of Aqidah Akhlak teaching materials. In order to get these results there are several ways that are used, namely validating material experts with an eligibility percentage of 80%, while validation by media experts is 85.4%. In addition, the results of trials for class XI MA students using this teaching material produced a score of 84.4%. So based on the description above, the analysis of product development results is stated to be valid and effective.